Reproductive life events in the population living in the vicinity of a nuclear waste reprocessing plant. Issue 6 (13th May 2008) - Slama, R; Boutou, O; Ducot, B; Spira, A
Abstract : Objective: There is concern about the health of populations living close to nuclear waste reprocessing plants. A comparative study was conducted on reproductive life events in the general population living near the nuclear waste reprocessing plant in Beaumont-Hague, France and a reference area in Brittany. Design, setting and participants: Women were randomly selected and retrospectively questioned on reproductive life events occurring between 1985 and 2000. The monthly probability of pregnancy (assessed by time to pregnancy for pregnancy attempts leading or not to a live birth), occurrence of involuntary infertility, miscarriage and birth weight were compared between both areas using regression models with random effect. Results: Compared with the reference area (326 couples) and after adjustment for sociodemographic and behavioural factors, couples from Beaumont-Hague (857 couples) had an estimated hazard ratio of pregnancy of 1.19 (95% CI 0.89 to 1.58). The prevalence ratio of 12-month involuntary infertility was 0.99 (95% CI 0.64 to 1.55) and the odds ratio of miscarriage was 0.86 (95% CI 0.85 to 1.33) for Beaumont-Hague, compared with the reference area. Mean birth weight was similar in both areas (95% CI of difference −85 g to 53 g). Conclusion: No increased risk of adverse reproductive life events was highlighted in the population living in the vicinity of the French nuclear waste reprocessing plant, compared with the reference area. Reproductive health is unlikely to be strongly altered in the general population of Beaumont-Hague.